Visual Communication of Murals - Ari, Ida Ayu Dwita Krisna; Nuriarta, I Wayan (COMMUSTY Journal of Communication Studies and Society, 2022)
The aim of this study is to describe the visual communication of mural in Tamanbali village, Bangli-Bali. The mural in Tamanbali village is a visual communication work that conveys information and persuades the public to always follow the health protocols during this Covid-19 pandemic. This study used a qualitative design. Everything related to the mural made by the 2021 Community Services Programme students of Indonesian Institute of the Art Denpasar in Tamanbali village, Bangli regency will be describe qualitatively. The subject of this research is a mural made by the 2021 Community Services Programme students of Indonesian Institute of the Art Denpasar inTamanbali village, Bangli. The object of this research focus on analyzing the illustration, typography, colour, and layout as well as the denotative and connotative meaning. The presence of the mural in Tamanbali village, Bangli made by the 2021 Community Services Programme students of Indonesian Institute of the Art Denpasar is a form of visual communication work that effective in conveying messages. The mural that presents the social problem related to the corona virus becomes an effective way to persuade and inform the public to always be aware of the spread of the corona virus. This mural reminds Tamanbali residents and the people in general to always follow the health protocols in various actions. The health protocols mentioned above, such as maintaining distance between one another during meetings, always wearing a mask, and also washing hands regularly to maintain cleanliness.